2016
DOI: 10.1007/s12020-015-0848-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-species sequence comparison reveals conservation of ghrelin gene-derived splice variants encoding a truncated ghrelin peptide

Abstract: The peptide hormone ghrelin is a potent orexigen produced predominantly in the stomach. It has a number of other biological actions, including roles in appetite stimulation, energy balance, the stimulation of growth hormone release and the regulation of cell proliferation. Recently, several ghrelin gene splice variants have been described. Here, we attempted to identify conserved alternative splicing of the ghrelin gene by cross-species sequence comparisons. We identified a novel human exon 2-deleted variant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The major bioactive product of the ghrelin gene seems to be ghrelin; however, ghrelin gene displays a complex transcriptional pattern that also generates mRNA transcripts that do not code for ghrelin, but instead for C-terminal region of pre-proghrelin, splice variants that differ in their 5′ untranslated regions and antisense transcripts [83,90,91]. Some of the alternative ghrelin mRNA transcript variants include the in1-ghrelin transcript that retains the intron 1 leading to a truncated form of ghrelin, the ex2-deleted ghrelin transcript that lacks exon 2 and also leads to a truncated form of ghrelin, the ex3-deleted ghrelin transcript that lacks the exon 3 containing the coding region for obestatin, and the in2c-ghrelin transcript that contains the coding region for ghrelin and an intron 2-derived sequence but lacks the obestatin sequence [92,93,94,95]. …”
Section: Ghrelin Synthesismentioning
confidence: 99%
“…The major bioactive product of the ghrelin gene seems to be ghrelin; however, ghrelin gene displays a complex transcriptional pattern that also generates mRNA transcripts that do not code for ghrelin, but instead for C-terminal region of pre-proghrelin, splice variants that differ in their 5′ untranslated regions and antisense transcripts [83,90,91]. Some of the alternative ghrelin mRNA transcript variants include the in1-ghrelin transcript that retains the intron 1 leading to a truncated form of ghrelin, the ex2-deleted ghrelin transcript that lacks exon 2 and also leads to a truncated form of ghrelin, the ex3-deleted ghrelin transcript that lacks the exon 3 containing the coding region for obestatin, and the in2c-ghrelin transcript that contains the coding region for ghrelin and an intron 2-derived sequence but lacks the obestatin sequence [92,93,94,95]. …”
Section: Ghrelin Synthesismentioning
confidence: 99%
“…2015; Gutierrez et al, 2008; Romero et al, 2010; Mohan and Unniappan, 2013). GOAT is conserved across a variety of vertebrate, including mice ( Mus musculus ), rats ( Rattus norvegicus ), domestic chickens ( Gallus domesticus ) and goldfish ( Carassius auratus ) (Gutierrez et al, 2008; Seim et al, 2016; Blanco et al, 2017). Furthermore it appears that a truncated form of GHSR1a, GHSR1b, is also cleaved from the same gene and has been reported to reduce cell surface GHSR1a availability via heterodimerization (Chow et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Goymann et al, (2017) reported that acylated plasma ghrelin predicts lipid content in garden warblers ( Sylvia borin ) and that unacylated ghrelin administration increases migratory restlessness behavior, suggesting that the differences in ghrelin mediation of energy homeostasis between avians and other animals may be due to migratory behavior. Although ghrelin is highly conserved across vertebrate (Seim et al, 2016), it is necessary to investigate the potential circuits that may contribute to species similarities and differences in ghrelin modulation of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of transcription are complex and fine-tuned by cell specific transcriptional networks, epigenetics, methylation and ubiquitination [ 80 82 ], cell turnover rates [ 83 ] and heterogeneities in the functional elements of transcription [ 84 ]. Moreover, mitochondrial dysfunction and retrograde response mechanisms have been identified as factors influential for changes in gene expression [ 85 87 ].…”
Section: Discussionmentioning
confidence: 99%